Implementasi Akad- Akad Syariah pada Produk Tabungan Haji dan Umroh di Bank Muamalat Cabang Parepare - Suci Rahmadani M; Hadiatullah, Hijrah; Nurfadillah, Alsyah; Husniati, Husniati; Dzacky Hamdan, Ahdani (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
This study aims to analyze the implementation of Sharia contracts applied in the Hajj and Umrah Savings products at Bank Muamalat Parepare Branch, which utilizes several main contracts, namely mudharabah mutlaqah, wadiah yad dhamanah, and ijarah, each having distinct functions and characteristics in managing customer funds. The approach used is qualitative descriptive, with data collected through in-depth interviews with management, direct observation, and documentation of bank policies and operational procedures. The results indicate that the implementation of these contracts aligns with the principles and fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), both in fund management, contract mechanisms, and customer services. However, challenges were identified such as customers' limited understanding of the differences between the contracts, necessitating more intensive Sharia education by the bank. This study emphasizes that the application of Sharia contracts must be implemented consistently not only formally but also by upholding the values and ethics of Islamic banking, which stress justice, transparency, and accountability. Customer education and strengthening the capacity of the bank’s human resources are crucial factors to ensure the sustainability and improvement of the quality of the Hajj and Umrah Savings products in accordance with the maqasid al-shariah (objectives of Sharia). Thus, this study contributes to the development of literature and practice in Sharia banking, particularly for ibadah savings products that require deep understanding and holistic, ethical service.